„A Russian choir that Russia had never heard before“: The Don Cossack Choir Serge Jaroff on the concert stage in the interwar Belgrade - Golubović Marija (Muzikologija, 2020)
After the October Revolution, the Russian tradition of spiritual and folk choral singing was introduced to the whole world by the active work of choirs that appeared in exile. The Don Cossack Choir Sergei Jaroff and the Metropolitan Choir of Alexander Nevsky Cathedral in Paris under Nikolai Afonsky, were two unique choirs that stood out over time. During the interwar period Jaroff’s Choir performed ten times in Belgrade with great success. The capital’s press announced them with great enthusiasm and the first Belgrade concert attracted the attention of significant critics such as Miloje Milojević, Branko Dragutinović,Viktor Novak, Jovan Dimitrijević and Petar Bingulac. The day after their first concert in Belgrade in January 1929, The Don Cossack Choir Serge Jaroff attended a reception at the King Alexander’s Court, who honored them on this occasion. The study of their performances in the 1920s and 1930s in Belgrade is based on domestic periodicals of that time and archival material from the Archives of Yugoslavia.